Unpacking Customer Satisfaction in Chengdu's Booming Food Delivery Scene: What Drives Success in the App Economy? - Zhang, Yingxue (Scholar: Human Sciences, 2026)
Purpose: This study aims to explore the key factors that significantly impact user satisfaction with Meituan's food delivery platform in Chengdu, China. Research design, data, and methodology: By integrating relevant theories and literature, a conceptual framework of variables such as information quality, price/value, safety, food quality, service quality, customer satisfaction, and customer loyalty was constructed to reveal the causal relationship between them. A quantitative method (n=500) was used to conduct a questionnaire survey on Meituan users in five districts of Chengdu. The sample was selected using a multi-stage sampling method, including judgment, stratified random, and convenience sampling. The data were analyzed by structural equation modeling (SEM) and confirmatory factor analysis (CFA), including model fitting, reliability, and validity tests. Results: The results showed that information quality significantly impacted price value, safety on customer satisfaction, food quality on customer satisfaction, service quality on customer satisfaction, and customer satisfaction on customer loyalty. Conclusions: The findings revealed that information quality significantly enhances price value, while safety, food quality, and service quality positively affect customer satisfaction. Furthermore, customer satisfaction has a significant positive effect on customer loyalty. However, the effects of price value and information quality on customer satisfaction were found to be insignificant.